Analisis Kalimat Imperatif dalam Novel Serial Bumi Sebagai Alternatif Bahan Pembelajaran Menulis Teks Petunjuk - Mutiara, Okta; Wardana, Deni; Widjojoko, Widjojoko (Universitas Pendidikan Indonesia Kampus Serang, 2023)
Imperative sentences are sentences that are intended for someone to do something according to the will of the person who gave the order. Apart from books and instructional texts that can be used to convey imperative sentences, there are other sources such as novels. This study intends to identify how imperative sentences are used in the novel Serial Bumi which is then used as learning material for writing instructional texts in the form of videos for fourth grade elementary school students. The type of technique and method used in this research is a qualitative approach with content analysis. Based on the results of the analysis, there are 140 imperative sentences which are divided into 12 types of imperative sentences in the novel Serial Bumi, namely imperative sentences of commands, orders, requests, urges, persuasion, appeals, requests, invitations, permits, prohibitions and hopes. Imperative sentences are classified from subtle to harsh statements. Hard commands usually end with an exclamation point, while soft commands end with an exclamation point but with a period. From the results of the analysis, it can be used in the manufacture of instructional text instruction materials for fourth grade elementary school students, indicating that the learning materials are writing.